Variasi Pemberian Bioton terhadap Kelimpahan Moina sp. - Anny Rimalia; Yulius Kisworo (Rawa Sains: Jurnal Sains STIPER Amuntai, 2020)
Fish after the egg-bag absorption phase require external feeding, in the form of fresh natural food organisms, such as phytoplankton, zooplankton, or aquatic insect larvae. These natural food organisms are limited in number. The business of mass production of natural food is still limited to several types originating from marine or brackish waters. For this type of natural freshwater fish feed, it is still limited to experimental materials. This study aims to determine the best dosage of Bioton liquid fertilizer added to the maintenance medium to the rate of population abundance of Moina sp. The research was conducted at the Wet Laboratory of Fisheries Cultivation Study Program, Faculty of Agriculture, Ahmad Yani University, Banjarmasin. The method used in this study was an experiment with a completely randomized design of 4 treatments and 3 replications. The treatment applied was 4 treatments with 3 repetitions, with the following treatment of Bioton liquid fertilizer: A = 5 ml / 3 l water, B = 10 ml / 3 l water, C = 15 ml / 3 l water, and D = without Bioton liquid fertilizer (control). The results showed that the abundance of Moina sp in treatment A = 4,333 ind / l, B = 3,633 ind / l, C = 2,700 ind / l and D = 3,034 ind / l. The ANOVA test results of all treatments were very significantly different, so accept H1, namely giving bioton with different doses had a significant effect on the abundance of Moina sp. The results of the LSD test of all treatments had a very significant difference in abundance, except for treatment D to treatment C which was significantly different, with the best treatment being a dose of 5 ml / 3 l of water (treatment A).